AAPM task group 224: Comprehensive proton therapy machine quality assurance. Issue 8 (14th June 2019) - Arjomandy, Bijan; Taylor, Paige; Ainsley, Christopher; Safai, Sairos; Sahoo, Narayan; Pankuch, Mark; Farr, Jonathan B.; Yong Park, Sung; Klein, Eric; Flanz, Jacob; Yorke, Ellen D.; Followill, David; et al.
Abstract : Purpose: Task Group (TG) 224 was established by the American Association of Physicists in Medicine's Science Council under the Radiation Therapy Committee and Work Group on Particle Beams. The group was charged with developing comprehensive quality assurance (QA) guidelines and recommendations for the three commonly employed proton therapy techniques for beam delivery: scattering, uniform scanning, and pencil beam scanning. This report supplements established QA guidelines for therapy machine performance for other widely used modalities, such as photons and electrons (TG 142, TG 40, TG 24, TG 22, TG 179, and Medical Physics Practice Guideline 2a) and shares their aims of ensuring the safe, accurate, and consistent delivery of radiation therapy dose distributions to patients. Methods: To provide a basis from which machine‐specific QA procedures can be developed, the report first describes the different delivery techniques and highlights the salient components of the related machine hardware. Depending on the particular machine hardware, certain procedures may be more or less important, and each institution should investigate its own situation. Results: In lieu of such investigations, this report identifies common beam parameters that are typically checked, along with the typical frequencies of those checks (daily, weekly, monthly, or annually). The rationale for choosing these checks and their frequencies is briefly described. Short descriptions of suggested tools and procedures for completing some of the periodic QA checks are also presented. Conclusion: Recommended tolerance limits for each of the recommended QA checks are tabulated, and are based on the literature and on consensus data from the clinical proton experience of the task group members. We hope that this and other reports will serve as a reference for clinical physicists wishing either to establish a proton therapy QA program or to evaluate an existing one.